Informality and Mobility: Evidence from Russian Panel Data - Fabian Slonimczyk; Vladimir Gimpelson (Institute for the Study of Labor (IZA), 2013)
Informality is a defining characteristic of labor markets in developing and transition countries. This paper analyzes patterns of mobility across different forms of formal and informal employment in Russia. Using the RLMS household panel we estimate a dynamic multinomial logit model with individual heterogeneity and correct for the initial conditions problem. Simulations show that structural state dependence is weak and that transition rates from informal to formal employment are not lower than from other origin states. These results lend support to the integrated view of the labor market.
Keywords: J6; 330; informality; labor mobility; initial conditions problem; state dependence